4D visualization to bridge the knowing-doing gap in megaprojects: an Australian case study (Construction Economics and Building, 2020)
The literature on megaprojects are oriented towards ‘knowing’ the problems and ‘knowing’ the solutions, and there is a dearth in literature aimed at explaining strategies adopted in ‘doing’ or implementing that knowledge. Particularly, the literature highlights communication as important as part of the ‘knowing,’ while there is a gap in ‘doing,’ as performance improvements are still not evident. This research aims to explore how this knowing-doing gap in the communication of risk information was addressed by using 4D visualization. This article discusses the vent facility of a megaproject in Australia as a case study to illustrate the innovation. The 4D model developed for the facility helped the project team to visualize the construction of a critical part of the project, discuss the construction methodology, identify the risks in the construction process and persuade the non-technical decision-makers of the project to take appropriate action. The risks identified through the visualization covered safety, program, and interface risks. This study offers insights into the role of visualization in bridging the knowing-doing gap in the construction industry in the context of a megaproject.